Architectural Decor of the Ancient Zhetysu Turks (VII−XIII centuries.) - Nurzhanov Arnabay A. (Археология евразийских степей, 2021)
This article describes the architectural decor of Zhetysu ancient Turks (on example of the medieval city-site Kulan).The cities’ formation and development in Central Asia and on Kazakhstan territory, with all the general laws, had its own characteristics. This conclusion is especially important for medieval Kazakhstan, where the formation of urban centers took place in the context of the historically established interaction of a sedentary agricultural and nomadic population, which affected the topography and types of cities, the urban culture’s originality. Artistic carved clay that adorned the interiors of monumental buildings in the medieval towns of Zhetysu (Semirechye) is a unique material. It is generally accepted that it was used as a way of expressing the religious, mythological and secular worldview aspects. For some cultures, in solving issues of ideology and art, carved clay is one of the main sources, since other sources are either absent or too fragmentary.